2020
DOI: 10.7717/peerj.8559
|View full text |Cite
|
Sign up to set email alerts
|

Sound production in the Meagre,Argyrosomus regius(Asso, 1801): intraspecific variability associated with size, sex and context

Abstract: Background Many fish taxa produce sound in voluntary and in disturbance contexts but information on the full acoustic repertoire is lacking for most species. Yet, this knowledge is critical to enable monitoring fish populations in nature through acoustic monitoring. Methods In this study we characterized the sounds emitted during disturbance and voluntary contexts by juvenile and adult meagre, Argyrosomus regius, in laboratory conditions. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
4
14
0
Order By: Relevance
“…In accordance with recent studies [41][42][43], it was here demonstrated that the meagre vocal repertoire is wider than previously thought [37]. Furthermore, fine acoustic features of grunts emitted during spawning nights are overall consistent between Portuguese and Mediterranean French populations [55].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In accordance with recent studies [41][42][43], it was here demonstrated that the meagre vocal repertoire is wider than previously thought [37]. Furthermore, fine acoustic features of grunts emitted during spawning nights are overall consistent between Portuguese and Mediterranean French populations [55].…”
Section: Discussionsupporting
confidence: 91%
“…Here we tried to evaluate the validity of sound categories using both classifications (onomatopoeic and context of emission). Our study supports that the vocal repertoire of the meagre is wider than previously thought [37], in accordance with more recent studies [41][42][43]. Lagardère and Mariani [37] reported the presence of short grunts (pulsed sounds ranging from 4 to 6 pulses) and of long grunts (pulsed sounds of more than 30 pulses).…”
Section: Plos Onesupporting
confidence: 93%
See 2 more Smart Citations
“…However, there are several species including Micropogonias undulatus , Micropogonias furnieri , Argyrosomus japonicus , Larimichthys crocea , and Pogonias cromis 12 , 16 19 in which both sexes possess sonic muscles although muscles are larger in male Atlantic croaker 12 . Female sound production in M. furnieri and Pogonias cromis has been evoked by holding or chasing them 18 , 19 , and male and female Japanese croaker Argyrosomus japonicus and meagre Argyrosomus regius produce sounds during the mating season 3 , 20 . Otherwise female sound production has not been studied in the family.…”
Section: Introductionmentioning
confidence: 99%